2018
DOI: 10.1111/hepr.13063
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of stereotactic body radiotherapy for patients with small hepatocellular carcinoma

Abstract: Aim:To evaluate the long-term outcome of stereotactic body radiotherapy in patients with small hepatocellular carcinoma who were ineligible for resection or ablation therapies.Methods: A total of 65 patients with 74 hepatocellular carcinomas (median tumor size 16 mm) were enrolled in the present study. They were treated with the prescribed dose of 48 Gy in four fractions at the isocenter. We extended the observation period and analyzed long-term outcomes, including overall survival, progression-free survival, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 22 publications
(36 reference statements)
3
35
0
Order By: Relevance
“…SBRT is applied in patients with lesions which is located near to the central portal area and close to hepatic vessels and near to the biliary system. SBRT is primarily used in the patients with small HCC who cannot undergo to surgery, RFA, or transplantation [52] .…”
Section: Early Stage Treatmentmentioning
confidence: 99%
“…SBRT is applied in patients with lesions which is located near to the central portal area and close to hepatic vessels and near to the biliary system. SBRT is primarily used in the patients with small HCC who cannot undergo to surgery, RFA, or transplantation [52] .…”
Section: Early Stage Treatmentmentioning
confidence: 99%
“…Prospective and retrospective studies of SBRT in patients with BCLC Stage A HCC demonstrate excellent local control rates (►Table 1). 45,[48][49][50][51][52][53] In this population, SBRT is commonly performed as salvage treatment after RFA failure or for tumors ineligible for ablation due to size, location, or ultrasound visibility. An early prospective trial from the Netherlands treated eight HCC patients with single lesions up to 7 cm with CP Class A or no cirrhosis and found 1-year local control rates of 80%.…”
Section: Efficacy and Safety Of Sbrt And Additional Data Needed Localmentioning
confidence: 99%
“…50 In contrast, grade 3 or higher toxicities were reported as 11% in the Indiana University CP Class A patients, 16% in the Netherlands study, 23.1% in the Hiroshima University study, and 38% in the Indiana University CP Class B patients. 48,49,51,52 There are likely institutionspecific differences in balancing the trade-offs between patient selection, tumor dose escalation, and conservative dosing of the unaffected bowel and liver, as well as potential biological differences in liver sensitivity to RT between regions due to the endemic hepatitis B in Asia. More information is required to elucidate the differences.…”
Section: Efficacy and Safety Of Sbrt And Additional Data Needed Localmentioning
confidence: 99%
“…Previous studies have reported that the natural median survival time of patients with HCC and PVTT is 2-4 months [8,9]. Several clinical studies have con rmed that radiotherapy is effective for treating HCC with PVTT [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Stereotactic body radiotherapy (SBRT) has emerged as a new radiotherapy technology that can deliver high doses of radiation to the target area in fewer fractions [13][14][15]. SBRT can accurately transfer a large dose of multiple beams to the target tumor within 1 to 5 fractions, owing to technical progress in accurate dose transfer, respiratory movement management, and daily image guidance.…”
Section: Introductionmentioning
confidence: 99%